A long-run relationship between the trade and its determinants for a group of selected Arab Maghreb Union Countries - Abdullah, Hussin; Abdullah, Norehan; Abuhriba, Hadi Mohamad Othman (European Centre for Research Training and Development UK, 2013)
The Arab Maghreb Union (AMU) comprising Algeria, Libya, Mauritania, Morocco, and Tunisia has established a framework to enhance regional cooperation on trade facilitation. It is doubtful whether the Arab Maghreb countries could achieve the goals of this regional cooperation or not. The objective of this study is to examine a long-run relationship between the trade and its determinants for a group of selected Arab Maghreb Union Countries.Using a data set consisting of a panel observation for the AMU countries for the period of 1989-2009; a panel unit root test was done to investigate the possibility of panel cointegration.Overall, the results are consistent with those found in Pedroni approach in all cases, parameters for the variables are found to be correctly signed and highly significant. In terms of trade openness, the results show that the trade barriers are found to be positively and significantly correlated with openness where their relationships within the AMU trade intensity ratios show a strong correlation.In other words, the trade barriers are fairly effective for increasing trade.